Halophilic bacteria from low and high intertidal zone of mangrove soil in Blue Lagoon, Port Dickson, Negeri Sembilan / Nur Zahra Zainal Fuadi, Siti Khadijah Azmi and Ilyanie Hj Yaacob - Zainal Fuadi, Nur Zahra; Azmi, Siti Khadijah; Yaacob, Ilyanie (Universiti Teknologi MARA, Negeri Sembilan, 2023)
Mangroves are among the world's most productive marine ecosystems, providing a distinctive habitat for many species as well as essential services and supplies for humans. Mangroves are believed to be one of the most specialized ecological abundances of halophytic plants, appearing as a transition zone between land and sea. Mangrove forests have a unique ecosystem that can dwell in a challenging environment with limited oxygen levels in the water (Othman & Wan Daud, 2018). Mangroves spend most of their life period submerged in seawater, where the sea level affecting the mangroves varies depending on the tidal surges (Wan Ahmad et al., 2018). Since mangroves are capable of living in high-salinity environments, microorganisms such as halophiles exist in the rhizosphere of the mangrove forests.